Assisting Domestic Industries under International Oligopoly: The Relevance of the Nature of Competition to Optimal Policies - Cheng, Leonard K. (American Economic Review, 1988)
Optimal trade and industrial policies are derived for a home market that is supplied by a domestic firm and a foreign firm. The optimal policy combination can be quite sensitive to the nature of the duopoly's competition. For example, for some cost and demand s tructures, the optimal policy under Cournot competition consists of a domestic production tax and a tariff, but that under Bertrand compet ition consists of a production subsidy and free trade. Copyright 1988 by American Economic Association.